Occupational contact allergy to omeprazole and ranitidine - Inmaculada Herrera-Mozo; Pere Sanz-Gallen; Gabriel Martí-Amengual (Nofer Institute of Occupational Medicine, 2017)
Omeprazole is a proton pump inhibition and ranitidine is an H2 histamine receptor antagonist widely used in the treatment of gastroesophageal reflex disease, peptic ulcer disease, Zollinger-Ellison syndrome and as a protector of the gastric mucosae. We report a case of occupational contact allergy to omeprazole and ranitidine. A 48-year-old man, with no pre-existing history of atopy or lifestyle factors. He neither had any medical history of consumption of drugs such as ranitidine and omeprazole. He worked for 19 months in the pharmaceutical company that manufactured ranitidine base. He presented rash in the face and eczema on the dorsum of the hands with itching. The study by prick tests with ranitidine gave negative response. Patch testing with ranitidine base and ranitidine hydrochloride gave positive response. A month later, when the patient was asymptomatic he returned to the pharmaceutical company, being switched from this previous job to the reactor manufacturing omeprazole. A few days after that, he presented erythematous eruptions involving face and neck with itching. Prick tests, path tests and in vitro laboratories studies with omeprazole gave positives. In this case the patient presented hypersensitivity type I at omeprazole and hypersensitivity type IV at omeprazole and ranitidine. Our aportation indicates the importance of careful analysis of the occupational exposure histories of patients with the suspected type I or type IV hypersensitivity to allergens, to determine whether work exposure is the cause. Med Pr 2017;68(3):433-435